2017
DOI: 10.1051/epjconf/201715900002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of gas flow and droplet motion in a wave-plate eliminator of the separator-steam-generator system in the waste-heat-utilisation complex

Abstract: Abstract. This paper studied the droplet transport and deposition in the turbulent flow inside a wave-plate eliminator of the waste-heat utilisation complex (WHUC). The Lagrangian discrete particle approach was used to simulate the process of liquid separation from wet steam flow. Two different models for droplet-eddy interaction were tested using data from the available literature. The tested numerical model was used to predict the WHUC performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The researchers have conducted a large number of simulation studies for corrugated plate gas–liquid separators by randomly combining different turbulence models, grid forms, wall treatment methods, and differential formats. By comparing the simulation results with the experimental data, they found that the grid format has little effect on the results, the simulation results in higher-order difference format are more accurate, the simulation of the flow field is more accurate, and the prediction of small droplets is better when the enhanced wall function is used; thus, a mature simulation calculation method is established. Scholars at home and abroad have studied the influence law of the single-hook corrugated plate drainage hook height, length, and angle and the interaction between the three on the separator performance and optimized the structural parameters of the single-hook corrugated plate drainage hook. The researchers have studied different structure types of front and rear drainage hooks for the double-hook corrugated plate, analyzed the advantages of different structures by the effects of drainage hooks on velocity, pressure, turbulent kinetic energy, and separation efficiency, and optimized the design using the response surface method. In the research process, single-hook and double-hook corrugated plates are usually studied separately, the advantages and disadvantages of their performance are determined singularly, and the comparative analysis of the performance of single-hook and double-hook corrugated plates is lacking. Moreover, the numerical simulation study of a corrugated plate with hooks mainly focuses on the optimization design, and the investigation of the action mechanism of drainage hooks is insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers have conducted a large number of simulation studies for corrugated plate gas–liquid separators by randomly combining different turbulence models, grid forms, wall treatment methods, and differential formats. By comparing the simulation results with the experimental data, they found that the grid format has little effect on the results, the simulation results in higher-order difference format are more accurate, the simulation of the flow field is more accurate, and the prediction of small droplets is better when the enhanced wall function is used; thus, a mature simulation calculation method is established. Scholars at home and abroad have studied the influence law of the single-hook corrugated plate drainage hook height, length, and angle and the interaction between the three on the separator performance and optimized the structural parameters of the single-hook corrugated plate drainage hook. The researchers have studied different structure types of front and rear drainage hooks for the double-hook corrugated plate, analyzed the advantages of different structures by the effects of drainage hooks on velocity, pressure, turbulent kinetic energy, and separation efficiency, and optimized the design using the response surface method. In the research process, single-hook and double-hook corrugated plates are usually studied separately, the advantages and disadvantages of their performance are determined singularly, and the comparative analysis of the performance of single-hook and double-hook corrugated plates is lacking. Moreover, the numerical simulation study of a corrugated plate with hooks mainly focuses on the optimization design, and the investigation of the action mechanism of drainage hooks is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“… 25 27 Scholars at home and abroad have studied the influence law of the single-hook corrugated plate drainage hook height, length, and angle and the interaction between the three on the separator performance and optimized the structural parameters of the single-hook corrugated plate drainage hook. 28 31 The researchers have studied different structure types of front and rear drainage hooks for the double-hook corrugated plate, analyzed the advantages of different structures by the effects of drainage hooks on velocity, pressure, turbulent kinetic energy, and separation efficiency, and optimized the design using the response surface method. 32 − 35 In the research process, single-hook and double-hook corrugated plates are usually studied separately, the advantages and disadvantages of their performance are determined singularly, and the comparative analysis of the performance of single-hook and double-hook corrugated plates is lacking.…”
Section: Introductionmentioning
confidence: 99%